2009
DOI: 10.3109/03602530903209288
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability in hepatic drug glucuronidation: studies into the role of age, sex, enzyme inducers, and genetic polymorphism using the human liver bank as a model system

Abstract: The human liver bank has provided an invaluable model system for the study of interindividual variability in expression and activity of the major hepatic UGTs, including UGT1A1, 1A4, 1A6, 1A9, 2B7, and 2B15. Based on studies using UGT isoform selective probes, the rank order of activity variability is UGT 1A1 > 1A6 > 2B15 > 1A4 = 1A9 > 2B7 with coefficient of variation values ranging from 92% to 45%. Liver donor age, sex, enzyme inducers, and genetic polymorphism are factors that have been implicated as source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 89 publications
3
151
4
Order By: Relevance
“…Because many factors can affect UGT2B7 activity, the activity of this enzyme displays large individual variability, 21 which further results in that human liver microsomal DES glucuronidation activity displays significant individual differences with DES glucuronidation activity ranging from 0.01 to 3.0 nmol/min/mg ( Figure 7). This suggests that the toxicity may correspondingly exhibit large individual variability in UGT2B7 activity-dependent manner.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many factors can affect UGT2B7 activity, the activity of this enzyme displays large individual variability, 21 which further results in that human liver microsomal DES glucuronidation activity displays significant individual differences with DES glucuronidation activity ranging from 0.01 to 3.0 nmol/min/mg ( Figure 7). This suggests that the toxicity may correspondingly exhibit large individual variability in UGT2B7 activity-dependent manner.…”
Section: ■ Discussionmentioning
confidence: 99%
“…20 Many factors, such as polymorphism, age, and coadministrated compounds, can influence the activities of UGTs, which are often in isoformdependent manners. 21 Therefore, characterization of the UGTs responsible for glucuronidation of a toxicant is essential to understand the factors affecting the toxicities and to predict individual differences of potential toxicities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, expression of human hepatic UGT2 members (UGT2B4, 2B7, 2B10, 2B15 and 2B17) is in general higher than that of family 1 members [56,57]. UGT2 members are known to be involved in catabolism of steroids and bile acids.…”
Section: Species Differences Of Rat and Human Hepatic Ugt Induction Bmentioning
confidence: 99%
“…Studies of human liver banks revealed large interindividual variation of UGT activities [56]. However, underlying factors (LATFs, liver-enriched transcription factors as well as genetic diversity [64]) are difficult to distinguish.…”
Section: Species Differences Of Rat and Human Hepatic Ugt Induction Bmentioning
confidence: 99%
See 1 more Smart Citation